The Process of Forming Public Acceptance of Household Gas Networks: A Study on Domestic Energy Users - Charly Simanullang; Jahrizal; Lailan Tawila Berampu (Indonesian Journal of Business Analytics, 2026)
The development of the household gas network (jargas) supports the domestic energy transition, but its success depends on public acceptance, not just infrastructure. This qualitative research with grounded theory explores the process of receiving gas networks through interviews, observations, and documentation of active customers. The results showed that acceptance was formed from the interaction of benefit perception (convenience, efficiency, continuity), positive user experience, trust in the service, and social legitimacy in the community. Customer experience and social dynamics are proven to strengthen service adoption. These findings contribute to the study of energy consumer behavior and the marketing of public utility services.